Learning Indonesian Becomes Fun: Creative Exploration with Methods Picture and Picture in Elementary School - Januar, Exsaris; Yati, Febrita Candra; Dahliana, Dina; Ratih, Maistika; Yumna, Yumna; Tulljanah, Rahmia (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
This research aims to explore the effectiveness of the Picture and Picture method in learning Indonesian in class V elementary school. This method is expected to increase students' interest and motivation in learning languages, as well as facilitate understanding of concepts in a more creative and fun way. Through an interactive visual approach, students are invited to collaborate in depicting stories and ideas using pictures, so that the learning process becomes more interesting. The type of research used is Classroom Action Research with data collection through observation, tests and documentation which are analyzed descriptively. The results of the research were marked by the achievement of indicators of success in classroom action research and an increase in the average score of students in Cycle I of Meeting II of 70.53, increasing to 72.11 in Cycle II of Meeting I and increasing again to 81.32 in cycle II Meeting II. The percentage of completion of Indonesian language learning results in Cycle I, Meeting I was 63.16%, increased in Cycle II, Meeting I by 78.95%, and increased again by 94.74% in Cycle II, Meeting II. It is hoped that these findings can make a positive contribution to the development of language learning methods in elementary schools.